Kick-off presentation of the project "PCMs4Buildings" - Systems with PCM-filled rectangular cavities for the storage of solar thermal energy for buildings - Soares, N. (2016)
This paper aims to provide a kick-off presentation of the project “PCMs4Buildings” - Systems with PCM-filled rectangular cavities for the storage of solar thermal energy for buildings. The main goal of this project is to develop a CFD methodology for the parametric analysis of the thermal behaviour of new TES systems with rectangular cavities filled with phase change materials (PCMs). These systems are designed to improve the energy performance of buildings. The project also intends to define full-scale prototypes to be numerically and experimentally optimized. “PCMs- 4Buildings” is a challenging project involving researchers from different scientific backgrounds, namely civil, mechanical and chemical engineering and two institutions, the Association for the Development of Industrial Aerodynamics (ADAI) and the University of Coimbra (UC). It also involves three research units, the Associate Laboratory of Energy, Transports and Aeronautics (LAETA), the Institute for Sustainability and Innovation in Structural Engineering (ISISE) and the Chemical Process Engineering and Forest Products Research Centre (CIEPQPF).